Molecular diagnosis and preimplantation genetic testing for chromosome 1q21.1 recurrent microduplication - Peng, Cuiting; Chen, Han; Zhou, Fan; Yang, Hong; Li, Yutong; Keqie, Yuezhi; Zhao, Xu; Wang, He; Hu, Ting; Liu, Shanling; Ren, Jun; Chen, Xinlian (Frontiers in Genetics, 2025)
As the development of molecular diagnostic methods, a large number of clinically relevant or disease-related copy number variations (CNVs) could be detected, and the demand for genetic counselling and clinical treatment is also increasing. For patients with pathogenic or likely pathogenic CNVs, preimplantation genetic testing (PGT) could provide a feasible path to prevent the inheritance of the genetic disorder in the offspring. In this study, we included a couple with 1q21.1 recurrent microduplication to conduct molecular diagnosis and PGT clinical application. The optical genome mapping (OGM) successfully verified the orientation and location of the microduplication, which further proved OGM as a promising approach for chromosomal anomalies detection with high resolutions. In PGT application, linkage-analysis-based PGT and high resolution PGT-A were simultaneously conducted for the pedigree and all the embryos. The results were consistent between linkage analysis and high resolution aneuploid analysis in the targeted region. One embryo that was absent of paternal 1q21.1q21.2 duplication was selected for further transplantation. This successful clinical practice in this study shed light for future molecular diagnosis and PGT application in tandem microduplications.